PALYNOLOGICAL STUDIES OF WINTER WEEDS MELLIFEROUS FLORA OF DISTRICT BANNU, KHYBER PAKHTUNKHWA, PAKISTAN - Ahmad, S.; Zafar, M.; Ahmad, M.; Ozdemir, F. A.; ., Lubna; Yaseen, G.; Sultana, S.; Kutlu, M. A. (Annali di Botanica, 2020)
The aim of the present study is to investigate the palynological features of the weeds from melliferous point of view. A total of 16 weeds, belonging to 10 different families were collected, pressed, identified and then analyzed microscopically. Both quantitative and qualitative characters of the pollen grains were examined including polar and equatorial diameter, P/E ratio, number of spines, number of colpi and pores, exine thickness and shapes of the pollen in both polar and equatorial view, using Leica microscope fitted with camera Meiji Infnity 1 and then analyzed statistically using software IBM SPSS Statistics 20. The results of the present study highlighted the signifcance of pollen morphology of the weeds as a bee ﬂora which may lead to the identifcation of the potential and useful weeds for bee keepers and to increase the honey production from the study area.